Recovery of low lactose goat's milk using cross-flow ultrafiltration membran - Zainul Abidin, Nur Sofuwani (2016)
An extensive amount of research has reported on the use of ultrafiltration (UF) membrane, particularly in the improvement of membrane performance efficiency on cow’s milk. However, a very limited number of researches reported on using UF for producing low-lactose goat’s milk due to inherently low lactose. Nonetheless, goat’s milk is still not suitable to be consumed in a large amount by people who are lactose intolerant, especially among Asians, where over 90% of the populations are suffering from lactose intolerance. Until today, fouling and concentration polarization (CP) on membrane surface in cross-flow hollow fiber UF unit are the major problems in the dairy industry. Discovery on how to overcome the problem is still in a hot debate due to the nature’s complex composition in milk. One way to overcome this problem is by evaluating the effects of processing parameters such as trans-membrane pressure (TMP) and feed-flow rate on flux (J), lactose rejection (Ri), concentration factor (CF), and accumulation rate (AR) during the fractionation of lactose. In terms of lactose fractionation for 5 KDa and 10 KDa UF membranes, the TMPs examined were 0.41, 0.55, and 0.69 bars, while feed flow-rates examined were 0.18, 0.34, 0.54, and 0.74 L/min. 5 KDa membrane shows that feed flowrate and flux behave in a direct relationship, while an inverse relationship in 10 KDa membrane. Both membranes showed that TMP 0.55 bar exhibit the best flux value without reaching the limiting flux region, but with feed flow rate of 0.74 L/min in 5 KDa, while 0.18 L/min in 10 KDa membrane. In statistical analysis software (SAS), feed flow-rate of 0.74 L/min was significantly greater (P < 0.05) in 5 KDa, while in 10 KDa membrane, flow-rate of 0.18 L/min gave the best condition (P < 0.05) that required in the lactose fractionation. Lactose rejection percentage (%Ri) is the lowest with 77.71% in 5 KDa membrane while 66.28% in 10 KDa membrane. This can be summarized that the best parameters for 5 KDa membrane is at TMP 0.55 bar with feed flowrate of 0.74 L/min, while for 10 KDa membrane is at TMP 0.55 bar with feed flowrate of 0.18 L/min. Due to higher flux value and lowest lactose rejection obtained from low feed flow-rate, 10 KDa UF membrane size was chosen over 5 KDa. The competitiveness between the concentrated milk obtained from 10 KDa UF membrane in this study and the commercial milk powder were compared in terms of nutrition facts and lactose concentration. The concentrated milk contained 5.63 g per 100 ml lactose concentration, which ranked at the second lowest concentration in the range of 2.81 to 7.91 g per 100 ml, proved that it is similar and comparable in standard as to commercial milk. As a conclusion, a high degree of lactose removal from goat’s milk could be achieved by 10 KDa UF membrane in a cross-flow hollow fiber system, which proved that different outcomes between 5 KDa and 10 KDa membranes and feed flow-rate required is closely associated to UF pore size and molecular weight of feed solute particles.